Glaciological and Meteorological Conditions at the Chinese Taishan Station, East Antarctica - Tang, Xueyuan; Guo, Jingxue; Dou, Yinke; Zhang, Yuzhong; Cheng, Siyuan; Luo, Kun; Yu, Lejiang; Cui, Xiangbin; Li, Lin; Zhang, Shengkai; Sun, Bo (Frontiers in Earth Science, 2020)
The glacio-meteorological characteristics of Princess Elizabeth Land in East Antarctica are poorly known due to a lack of measurement. This is problematic given the importance of this area for understanding ice sheet dynamics and climate change. We present a comprehensive approach (including field surveys, reanalysis data, remote sensing, and ice flow models) to investigate the glaciological and meteorological conditions in the vicinity of the new Chinese Taishan Station (73.864°S, 76.974°E) in Princess Elizabeth Land. We collected the datasets of satellite-derived ice surface velocities, surface mass balance, and wind field; mapped the ice thickness and internal layers around the Taishan Station site; and constructed profiles of the surface snow temperature and snow density. Also, we used transient thermodynamical 1-D vertical models to simulate the age of ice and the basal temperature with surface meteorological data and subglacial topography as boundary conditions. These investigations showed that Taishan Station is subject to a relatively high wind velocity, low temperatures (about -36 °C), and simple ice flow. The well-behaved internal layer stratigraphy implies that the ice flow of Taishan Station has been relatively stable, possibly for a long time. The fact that the internal layers are conformal with bed topography, there is a relatively higher basal ice age from ice modelling, and that the site lies over a bed depression filled with ice 1900 m thick, suggests that Taishan Station may be a good location for obtaining undisturbed old ice at depth. The combination of glacio-meteorological parameters suggests that Taishan Station is a potential drill site for the Chinese Antarctic Research Expedition (CHINARE) and an ideal logistical support location for proposed scientific field activities in the East Antarctic ice sheet (e.g. Dome A, Grove Mountains, and Princess Elizabeth Land).